Analysis of the Classification of Data on the Launch of Apple Mobile Phone Prices in China and Pakistan Using the Decision Tree Algorithm in Python Programming - Kevin Vincentio Benedict; Novi Rukhviyanti (Eduvest - Journal of Universal Studies, 2025)
This article explains the analysis of a data by studying data using data classification and applying the concept of the Decision Tree Algorithm and program tools that are done using python programming as a flexible and objective tool in an analysis and visualization of data in today's world of machine learning data requires good performance and good results in handling a data case. The data used is NoSQL data or Datasets has the form of a CSV document, which in the CSV document has tables where the results will be in the form of the latest datasets containing the datasets, namely by Data analysis, data classification, data classification, categorizing Apple mobile phone products in China and Pakistan Whether it is of high or low quality based on the launch of the price of Apple mobile phones, then building a decision tree modeling explaining the factor factor which affects the classification and helps analyze a launch of the price of Apple mobile phone products in China and Pakistan so that the results will be executed into python programming until this programming language has very good characteristics in the data process and until the data results will be visualized. Datasets will be tested, as well as supporting factors in python programming data modeling that provide flexibility in data modeling, data execution, data analysis so that problem solving can be solved properly and objectively.